The Effect of Isometric Training for the Quadriceps Femoris and Triceps Surae Muscles on the Ability to Jump Long Without Starting in Class XI MAN 1 Surakarta Students - Shella Dhika Rahmawati; Aulia Ayu Kusuma W; Lulu'ah Feby Purwanti (International Journal of Medicine and Health, 2023)
Athletics, as a very popular individual sport, is taught in high schools (SMA). Sport helps improve the functional development of all five senses, because during sport students are trained to be able to understand commands, rules of the game, work together, find solutions and seek goals. Long jump is a form of jumping movement lifting the legs up in front in an effort to carry the center of body weight as long as possible in the air or floating in the air which is done quickly and by pushing off one leg to reach the greatest distance possible. This research method uses experimental with "one group pre and post test design with control". The subjects of this research were 64 students of class XI MAN 1 Surakarta.